Is Whiteheadian Process Thought Compatible with Early Buddhist Philosophy? - Nyberg, Eric M. (Buddhist Christian studies, 2023)
Numerous authors have compared Process thought as articulated by Alfred North Whitehead and Mahayana Buddhist philosophy, owing to the fact that each of these systems is rooted in the notion that relational action, rather than substance, is meta-physically fundamental and that human life is to be understood as fundamentally experiential. However, despite the fact that the foundational philosophical tenets of Mahayana Buddhism are built on axioms established and rooted in early Buddhism, relatively little has been written comparing Process thought with the philosophy of early Buddhism. In this essay, I first offer a brief comparison and discussion of the foundational metaphysical principles of these systems. The purpose of this essay is to extend the dialogue between Process thought and early Buddhism, highlighting both areas of convergence and points of departure. The first task is to establish how key terms in each system may be understood in terms of the other and to point out ways in which these systems converge around questions of ontology, agency, and the nature of the self. I will then discuss the epistemologies that underwrite these meta-physical commitments. Finally, I will conclude with a brief comparison of the role of aesthetics in human experience and the soteriological project within these two schools of thought.